(untitled) (SAARC Journal of Agriculture, 2019)
An experiment was carried out using eight double cross F1s (DCF1s) as lines and two testers to obtain sixteen Line ×Tester hybrids for the evaluation of major growth and flowering traits thereby to understand the breeding potentiality of the parental lines. The performance of growth and flowering traits of all twenty-six genotypes were evaluated in a randomized complete block design (RCBD) with three replications. The analysis of variance (ANOVA) showed all the genotypes were significantly different for all agro-morphological traits under study. The estimated general combining ability (GCA) effects showed that parent 5(P5), were superior for plant height, stem diameter, number of leaves, leaf length, days to flowering and attitude of floral axis followed by parent 2(P2) for leaf length, leaf width, days to flowering and attitude of floral axis and parent7 (P7) for number of flower, flower diameter, bud length and attitude for floral axis. Likewise; tester 1 found to be best combiner with significant GCA effect for almost all growth and flowering traits (except number of leaves). The plant height, leaf width, number of flower and attitude of floral axis showed prevailing additive gene action while stem diameter, number of leaves, leaf length, days to flowering, flower diameter and bud length indicated predominance of dominance gene action. We can conclude that parent P5, parent P2 and parent P7 can be used as good mother lines and the tester 1, as good donor for the seed production. SAARC J. Agri., 17(1): 175-187 (2019)